Rekonstruksi Penataan Peraturan Perundang-Undangan Pasca Berlakunya Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan - Syahlan Syahlan (Wacana Hukum, 2019)
Synchronization and Harmonization of Regulations in Indonesia hadle by Badan Pembinaan Hukum Nasional and Direktorat Jenderal Peraturan Perundang-undangan. Stage of regulation’s synchronization and harmonization which doing by Badan Pembinaan Hukum Nasional are planning and preparation of Academic Text of regulation. Meanwhile, Direktorat Jenderal Peraturan Perundang-undangan will do synchronization and harmonization at the stage of draft of regulations by forming a Committee Between Ministries/Non-Ministries. The absence of a definite mechanism regarding the stages of synchronization and harmonization and do separately synchronization and harmonization in two institutions are not maximal. Finally, this pattern have an impact to quality of regulations which resulting which is the purpose of the synchronization and harmonization.